Impact of preheat zone properties on the flammability limits of crude biogas combustion in a two-layer porous radiant burner. (February 2020) - Devi, Sangjukta; Sahoo, Niranjan; Muthukumar, P
Abstract: The present work is aimed at comprehending the combustion phenomena of crude biogas in a Porous Radiant Burner (PRB), with varying properties of the porous inserts. In this regard, experimentation has been done on an in-house developed two layered PRB, incorporated with porous combustion zone (CZ) and preheat zone (PZ). Combustion in PRB is based on the concept of excess enthalpy where heat from the burnt products preheat the fresh fuel air mixture to give enhanced combustion. Hence, the porous inserts used in the PRB have a significant role to play in its performance characterization. This investigation is thus aimed at studying the effect of PZ porosity and thickness on the lean stable flame limits and the position of stable flame inside the PRB. The CZ was composed of SiC foam (porosity 90%), while straight hole Al2 O3 ceramic with varying porosity and thickness were used as the PZ for the test cases. The investigation was done for the varying input powers of 5 to 10 kW. Results indicate that PZ porosity and thickness has a significant influence on flame stability. One particular case, where the PZ porosity was 7% and thickness of 15 mm offered the best lean stable combustion, within the equivalence ration of 0.75-0.97.